Product Quality, Price, and Lifestyle as Determinants of Secondhand Clothing Purchase Decisions : Evidence from the Sunday Morning Market, Heroes Monument, Surabaya - Fadiyah Putri Rahmawati; Sarwani Sarwani; Dian Ferriswara; Fedianty Augustinah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The increasing trend of secondhand clothing consumption, commonly known as thrift shopping, reflects a major shift in consumer behavior. This study aims to analyze the influence of product quality, price, and lifestyle on consumers’ purchase decisions for secondhand clothing at the Tugu Pahlawan Sunday Morning Market in Surabaya. This research employed a quantitative approach using a non-probability sampling design. Primary data were obtained from 167 respondents through structured questionnaires utilizing a five-point Likert scale. Data analysis was conducted using multiple linear regression with the support of SPSS software, preceded by validity, reliability, and classical assumption tests. The results show that product quality, price, and lifestyle simultaneously have a significant influence on purchase decisions. Partially, product quality and lifestyle have a positive and significant effect, while price shows a weaker but still significant influence. These findings indicate that consumers’ decisions to purchase secondhand clothing are not solely driven by low prices but also influenced by perceived product quality and lifestyle preferences. This study contributes to the understanding of consumer behavior in informal markets and provides practical implications for business practitioners and policymakers to enhance sustainable consumption patterns.